A J-Protein OsDjC46 Interacts with ZFP36 to Participate in ABA-Mediated Antioxidant Defense in Rice - Xingxiu Huang; Liping Huang; Xixi Zhao; Jing Jia; Gang Zhang; Mengyao Zhang; Mingyi Jiang (MDPI AG, 2022)
ZFP36 has been shown to be involved in ABA-induced antioxidant defense and enhance rice tolerance to drought, salt stress and oxidative stress. Using ZFP36 as bait, a yeast two-hybrid system was used to obtain the interacting protein OsDjC46, which belongs to heat shock protein and usually exists in the form of molecular chaperone, was identified. Further Co-IP (co-immunoprecipitation), BiFC (bimolecular fluorescence complement) and GST (glutathione-S-transferase) pull-down experiments verified that ZFP36 interacted with OsDjC46 in vivo and in vitro. Heat shock protein has been shown to increase plant resistance to stresses, but whether OsDjC46 was a key factor in plant response to various stresses has not been reported. Here, various stimuli, such as abscisic acid (ABA), hydrogen peroxidase (H2O2), polyethylene (PEG) and sodium chloride (NaCl) markedly induced the expression of OsDjC46 in the seedlings. Overexpression of OsDjC46 in rice can enhance the tolerance to salinity and drought; in contrast, knockout of OsDjC46 rice plants was more sensitive to salt stress and drought. Further investigation revealed that OsDjC46 could participate in regulating the expression and activities of antioxidant of SOD and CAT under drought and salt stress. Taken together, these findings reveal a novel function of OsDjC46 in adjusting ABA-induced antioxidant defense.